Solid solution treatment on strength and corrosion of biodegradable Mg6Ag wires. Issue 2 (17th July 2017) - Maier, P.; Zimmermann, F.; Rinne, M.; Szakács, G.; Hort, N.; Vogt, C.
Abstract : A warm‐drawn Mg6Ag wire with a diameter of 1.6 mm is investigated by immersion tests in Ringer solution in two conditions: as‐drawn and solution heat‐treated wire. The initial as‐drawn condition showed higher strength in comparison to the solution heat‐treated one. As‐drawn wire has heavily twinned grains. Heat treatment causes slight grain growth, but less microgalvanic corrosion due to dissolved second phases and a significantly reduction of twin boundaries. The mean corrosion rate decreases by more than half by the heat treatment resulting in higher remaining mechanical properties. The mean corrosion rate also decreases with corrosion time, slightly more for the heat‐treated condition. Pitting corrosion was still present after solution heat treatment, although the pit shape is less harmful. The corroded wires and corrosion products were analysed qualitatively and quantitatively by SEM imaging and ICP‐OES with focus on the exposure time. Mg6Ag wires corrode under forming Mg(OH)2, CaCO3 and AgCl, SEM imaging proves higher corrosion resistance of heat‐treated Mg6Ag. Chemical analysis of wires, corrosion products and corrosion media offer to describe the time‐dependent mechanism. Abstract : Solution heat treatment improves corrosion resistance of Mg6Ag wires by dissolving second phases resulting in less microgalvanic corrosion potential and reducing twin boundaries, which are found in the as‐drawn condition. The corrosion rate decreases strongly by the heat treatment resulting in higher remaining mechanical properties. ICP‐OES is used to describe time depending corrosion mechanism.